Comparative Assessment of the Activity of Racemic and Dextrorotatory Forms of Thioctic (Alpha-Lipoic) Acid in Low Back Pain: Preclinical Results and Clinical Evidences From an Open Randomized Trial - Alessandra Pacini; Daniele Tomassoni; Elena Trallori; Laura Micheli; Francesco Amenta; Carla Ghelardini; Lorenzo Di Cesare Mannelli; Enea Traini (Frontiers Media S.A., 2021)
Peripheral neuropathies, characterized by altered nociceptive and muscular functions, are related to oxidative stress. Thioctic acid is a natural antioxidant existing as two optical isomers, but most clinically used as racemic mixture. The present study investigated the central nervous system's changes which followed loose-ligation-derived compression of sciatic nerve, the putative neuroprotective role of thioctic acid and the pain-alleviating effect on low-back pain suffering patients. Loose ligation of the right sciatic nerve was performed in spontaneously hypertensive rats (SHR), a model of increased oxidative stress, and in normotensive Wistar-Kyoto rats (WKY). Animals with sciatic nerve ligation were left untreated or were treated intraperitoneally for 15 days with 250 μmol·kg−1·die−1 of (+/−)-thioctic acid; 125 μmol·kg−1·die−1 of (+/−)-thioctic acid; 125 μmol·kg−1·die−1 of (+)-thioctic acid lysine salt; 125 μmol·kg−1·die−1 of (−)-thioctic acid; 300 μmol·kg−1·die−1 pregabalin. Control SHR and WKY rats received the same amounts of vehicle. The clinical trial NESTIORADE (Sensory-Motor Neuropathies of the Sciatic Nerve: Comparative evaluation of the effect of racemic and dextro-rotatory forms of thioctic acid) examined 100 patients (49 males and 51 females aged 53 ± 11 years) dividing them into two equal-numbered groups, each treated daily for 60 days with 600 mg of (+/−)-thioctic acid or (+)-thioctic acid, respectively. The trial was registered prior to patient enrollment at EudraCT website (OSSC Number: 2011-000964-81). In the preclinical study, (+)-thioctic acid was more active than (+/−)- or (−)-enantiomers in relieving pain and protecting peripheral nerve as well as in reducing oxidative stress and astrogliosis in the spinal cord. Main findings of NESTIORADE clinical trial showed a greater influence on painful symptomatology, a quicker recovery and a better impact on quality of life of (+)-thioctic acid vs. (+/−)-thioctic acid. These data may have a pharmacological and pharmacoeconomical relevance and suggest that thioctic acid, above all (+)-enantiomer, could be considered for treatment of low-back pain involving neuropathy.